THE IMPACT OF USING A SCIENTIFIC APPROACH ON READING COMPREHENSION OF SEVEN-GRADE STUDENTS - Siregar, Alfitriani (TELL - US JOURNAL, 2024)
The objective of this research was to examine the effects of using a scientific approach on the development of reading comprehension abilities among students in the seventh grade. The objective of this research was to ascertain the importance of using a scientific approach within the realm of reading comprehension. The current experimental study was carried out among a class of seventh-grade students at SMP Muhammadiyah 57 Medan during the academic year 2022-2023. The study population included a total of 47 students. The research used a random sample methodology. The experimental class for this research was designated as VII C and was subjected to the implementation of the scientific approach strategy. In contrast, the control class, VII A, was selected for the study and used the reading technique. The data gathering instrument was a blend of multiple-choice and essay forms. The data was obtained from pre-test and post-test evaluations of the pupils. A statistically significant difference was seen in the mean scores of students between the pre-test experimental class and the post-test experimental class. The data is shown by a two-tailed p-value of 0.000, which is lower than the preset significance threshold of 0.5. As a result, the incorporation of scientific methodology in educational research has a significant impact on the level of competency pupils have in reading and interpreting narrative texts. This, in turn, facilitates the enhancement of their analytical thinking and problem-solving skills, which are essential for their overall development.